Producer Soil Test Information Sheet - Rao S. Mylavarapu; William d'Angelo; Nancy Wilkinson (EDIS)
Revised! SL-135, a 2-page form for the UF/IFAS Extension Soil Testing Laboratory, must accompany soil samples submitted to the UF/IFAS Extension Soil Testing Laboratory by Florida agricultural producers. Includes important information for sample collection and submission, and crop and analysis codes. Published by the UF Department of Soil and Water Science, August 2007.